Pengaruh Model Pembelajaran Kooperatif Mind Mapping Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Tentang Biologi Di Kelas Ix Smp Negeri 6 Palu - Amalia Buntu; Achmad Ramadhan; Lilies N. Tangge (Universitas Tadulako, 2017)
The aims of this reaserch were explain the influence of mind mapping cooperative learning and learning motivation toward students learning outcomes about biology of IX grade student at SMP Negeri 6 Palu. This was a quantitative descriptive research with quasi experiment method. The taking of sample was done through random sampling. Each of groups consist of two class. The technique of data analysis used multiple regression. The result of data analysis indicate that partialy it was obtained X1 significant probability value was 0,00 < 0,05 and X2 significant probability value was 0,00 < 0,05. Simultane indicate the significant probability value was 0,00 < 0,05 so that mind mapping cooperative learning and learning motivation influence sinificantly toward the learning outcomes in biology either simultane and partial.